PERSONALITY OF BELLA IN TWILIGHT MOVIE DIRECTED BY CATHERINE HARDWICKE 2008: A PSYCHOANALYTIC APPROACH - FARINA, FADIL (2010)
The study elaborates the personality of Bella in Twilight movie by Catherine Hardwicke based on psychoanalytic approach. The aim of the study is to analyze the structural elements and the personality of Bella who chooses to live with her father or with a vampire. This study belongs to qualitative study. In this method, there are two types of data sources, which are used, namely primary data source and secondary data sources. The primary data source is the Twilight movie. Meanwhile, the secondary data sources are any literature related to the study. The researcher collects the data from both, primary and secondary data sources in a sort of document as evidence. The study uses library research to collect the data. The collected data are analyzed by means of descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, casting, sound, mise-en-scene, editing and cinematography are related to each other and form the unity into good quality of the movie. Second, based on the Psychoanalytic analysis, there is Bella's personality can be shown from conflict between id, ego and superego. There are three ids, three egos, and three superegos of Bella that appear in the story.